UMKM INDONESIAN ECONOMIC HEROES ACEH REGIONAL POLYTECHNIC STUDENT COMMUNICATION FORUM COMMUNITY SERVICES IN 2021 - Susanti; Hasbi; Armanda Butar Butar; Ajrul Amilin; Ahmad Saifullah (Lembaga Riset dan Inovasi Kreyat Center, 2023)
This pandemic has affected the socioeconomic in Indonesia, therefore it must be resolved immediately by involving all elements of the nation to save the Indonesian economy. Various efforts have been made by the government to restore economic performance in this country, but so far there have been no significant signs of national economic recovery. The existence of various government policies that have limited social interaction in the community in suppressing the spread of the pandemic in the country, this has resulted in a drastic reduction in public consumption which has contributed the most to Indonesia's economic growth. The other biggest impact is seen in the small and medium business sector and the informal sector which is the basis of the Indonesian economy. Nearly 59% of the significant decline occurred nationally. A Polytechnic is a form of tertiary institution besides an academy, institute, high school, and university. The Indonesian Polytechnic Student Communication Forum (FKMPI) Aceh Region carries its work program with the theme FKMPI Cares for UMKM with the aim of increasing student knowledge and insights about entrepreneurship, preparing superior human resources and being able to be globally competitive towards golden Indonesia 2045, Motivated to create job opportunities and educational institutions business and understand the concept of Social Entrepreneurship. This goal was achieved by educating Polytechnic students throughout Indonesia through a national seminar with the theme UMKM Heroes of the Indonesian Economy which took place online and offline.